Pengembangan Media Diorama berbasis STEAM untuk Meningkatkan Keterampilan Berpikir Kritis Siswa di Sekolah Dasar - Lailiyah, Nia Nur; Widiyono, Aan (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2023)
This exploration is inspired by decisive reasoning abilities and understudies' comprehension of the transformation learning of science material which isn't amplified because of the growing experience which actually doesn't utilize the right methodology and learning media. The motivation behind this review was to decide the attainability of STEAM-based lifelike model media to further develop the decisive reasoning abilities of 4th grade primary school understudies. This sort of examination is Innovative work (Research and development) research utilizing the Borg and Nerve model with 19 class IV understudies at SDN 5 Sinangul as subjects. The consequences of information examination showed that: ( 1) The approval consequences of media specialists, materials, and learning got a normal of 82%, 86%, and 90% so the establishment is truly practical, (2) The consequences of the viability of STEAM-based lifelike model media should be visible from positive understudy reactions and n-gain scores which show a low classification. This outcome implies that STEAM-based lifelike model media items to further develop the decisive reasoning abilities of 4th grade primary school understudies are legitimate, viable and powerful.